Breakdown characteristic of LLDPE-NR nanocomposite using high voltage direct current (HVDC) test - Mohd Jamail, Nor Akmal; Zarujhan, N.A.A.N.; Muhamad, N.A.
Polymer nanocomposite has attracted many researchers’ recently in which the materials were applied as insulation material since 21st century. Polymer nanocomposite was given more attention because of the material properties that can be drastically improved by adding a few percent of nano-sized filler. SiO2 and TiO2 these filler are listed as the main nanofiller commonly used in electrical engineering due to the increase of effective activation energy. Natural Rubber (NR) is used because it develops several interphases with Linear Low-Density Polyethylene (LLDPE) matrix. This paper primarily concern the outcome of the most effective performance of breakdown voltage between SiO2 and TiO2 nanofiller as solid insulation and the best percentage among 1 wt%, 3 wt%, 5 wt%, and 7 wt%. LLDPE-NR with the ratio composition of 80:20 was selected as the base polymer and has been conduct by using High Voltage Direct Current (HVDC) testing.